Awareness and Initiatives of Building Integrated Photovoltaic (BIPV) implementation in Malaysian Housing Industry. (2015) - Goh, K.C.; Yap, A.B.K.; Goh, H.H.; Seow, T.W.; Toh, T.C.
Abstract: Sustainability is a key concern among the Malaysian government today. Through the overlapping of the energy and construction sector, one of the initiatives that the government has done after research and development is the Building Integrated Photovoltaic (BIPV) program. However, though more than ten years have passed after the introduction of BIPV, the implementation is still considered very weak as it is still not a common practice in the construction industry. One of the reasons is because many are still sceptical about BIPV especially among house buyers and are more concern to the prices of the houses. The other factor is developers are dormant in using BIPV and have limited support in BIPV information that can convince house buyers make their decision to invest into BIPV. This research investigates the application issues faced by the developers, their outlook on BIPV and considerations for selection on BIPV. A three stage Delphi interview with eight developer companies as part of a purposive sample is applied, where stage one focuses on the application issues that is faced by developing and stage two the depth of the issues with workable solutions is proposed and validated among the developing consensus. Stage three helps mapping out crucial criteria of selection process that the developers will employ and other consideration towards BIPV. The preliminary results show that more establish developers have employed green technology, but none has considered BIPV yet with cost as a major factor in mind. Their process of selection is not established and individual has various interests that needed to be maintained. It can be concluded that developers indeed are a substantial catalyst for implementing BIPV. This study proposes a guideline to achieve a stronger implementation of BIPV for a more sustainable housing project among the developers.